Protection of new technology vaccine against Malaysia velogenic NDV GVII and GVIII isolates in broiler chickens - Bejo, Mohd Hair; L., Jessica T. M.; Saw, P. Y. (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Two experiments were conducted to determine the efficacy of a new technology vaccine, Vectormune® ND, a vector vaccine against Malaysia velogenic Newcastle disease virus (vNDV) genotypes VII (GVII) and VIII (GVIII) in broiler chickens. The study demonstrated that the vaccination programme could provide 100% protection to the chickens against GVII challenged at days 31 or 35 of age. Protection of 95% was achieved when the chicken were challenged with either GVII or GVIII at day 14 of age. The HI antibody titre and protection increased with time. GVII infected chickens in the unvaccinated group showed milder lesions with lower mortality rate when compared to the GVIII infected chickens. Torticollis was commonly recorded in chicken infected with GVII. It was concluded that a vaccination programme combining Vectormune® ND with a live attenuated ND/IB vaccine and a booster vaccination with La Sota is highly effective to provide protection to the chickens against GVII or GVIII challenged. Outbreaks of ND in the country is not due to failure of the NDV vaccine strains, but rather than due to other factors that lead to vaccination failures as well as poor vaccination strategy.